223k views
5 votes
What is the product? (4y − 3)(2y2 + 3y − 5)

1 Answer

1 vote

Answer: The required product is
8y^3+6y^2-29y+15.

Step-by-step explanation: We are given to find the following product :


P=(4y-3)(2y^2+3y-5).

To find the given product, we need to multiply each term of the first expression to each term of the second expression.

The multiplication is as follows :


P\\\\=(4y-3)(2y^2+3y-5)\\\\=4y(2y^2+3y-5)-3(2y^2+3y-5)\\\\=8y^3+12y^2-20y-6y^2-9y+15\\\\=8y^3+6y^2-29y+15.

Thus, the required product is
8y^3+6y^2-29y+15.

User Don Neufeld
by
5.4k points